THE KERCH STRAIT INCIDENT: IS THERE A BREACH OF INTERNATIONAL LAW? - Huang, Michelle Viandy (Legal Standing : Jurnal Ilmu Hukum, 2020)
On 23th November 2018, the Federal Security Service of the Russian Federation ("FSB") destroyed and captured three of Ukrainian Military Vessel, as well as detaining 24 of its personnels. As the dispute continues, Ukraine raised this matter to the International Tribunals on Law of The Sea (?ITLOS?), requesting a provisional measure pursuant to Article 280 paragraph 5 UNCLOS to release the vessels and personnels detained. ITLOS has made its order on 25th May 2019, ruling that Russia must release the detainee and return the vessels immediately to Ukraine. However, Russia refused to enforce the order and denied ITLOS jurisdiction over this matter due to the involvement of military aspect in the incident. Therefore, this paper provides an answer to the questions whether Russia?s act constitutes a violation to international law and whether ITLOS has the jurisdiction over the dispute.